AIOps in cloud computing: Automation performance Monitoring with AI and New Relic - Thota, Ravi chandra (International Journal of Scientific Research and Management (IJSRM), 2022)
AIOps technology used for IT operations delivers a cloud computing revolution through automated performance monitoring framework and proactive resolution of anomalies in systems. The traditional monitoring systems have difficulty managing the extensive scale and complexity of present-day cloud environments so they fail to deliver efficient incident management and optimize resources properly. The research investigates AIOps functionality in cloud environments while specifically analyzing the implementation of AI-based automation for performance surveillance through New Relic.The study explores how predictive analytics joined with machine learning models practice system observability and decreases human-based interactions to boost service reliability. Organizations who adopt AI-powered monitoring systems will identify operational patterns and forecast system breakdowns and optimize their cloud resource management in instantaneous manner. The AI-powered insights from New Relic provide users with complete KPI tracking capabilities that help maintain operational efficiency combined with reduced system downtime. The research presents AIOps advantage over traditional methods for cloud infrastructure management through an assessment involving both approaches. Research outcomes reveal that artificial intelligence boosts monitoring precision and accelerates root cause identification as well as supplying IT departments with intelligent decision capabilities. Studying AIOps enhances contemporary understanding of modern cloud systems and delivers real-world guidelines to companies that implement AI-driven monitoring solutions.